Plant growth promotion of the forage plant Lupinus albus Var. Orden Dorado using Pseudomonas agronomica sp. nov. and Bacillus pretiosus sp. nov. added over a valorized agricultural biowaste - Robas Mora, Marina; Fernández Pastrana, Vanesa M.; Oliva, Laura Luna Gutiérrez; Lobo, Agustín Probanza; Jiménez Gómez, Pedro A. (Frontiers in Microbiology, 2023)
The overexploitation of natural ecosystems and the evolution of climate change is currently forcing us to design new strategies for a more sustainable use of agronomic uses. Plant residue valorization can help palliate these problems, for example, through its use in biofertilizers as an alternative to chemical fertilizers. In this paper, the effect of the ORGAON® organic fertilizer matrix from the valorization of horticultural waste to which two PGPB (Plant Growth-Promoting Bacteria) strains are added is tested. The complexity of the biomolecules that constitute them explains the benefit that the addition of PGPB can induce in the transformation of those biomolecules, helping to prolonged adsorption of nutrients through the roots of the plants, favoring the direct and indirect promotion of plant growth. The efficacy of two new species (Bacillus pretiosus and Pseudomonas agronomica) on the biometric variables of inoculated plants of Lupinus albus Var. Orden Dorado is tested. Additionally, the phenotypic and PGP characteristics, fatty acid analysis, MALDI-TOF, genomic features (DNA-DNA hybridization, ANI) and phylogenetic analyzes using the housekeeping genes 16S rRNA, gyrB, rpoB and rpoD are described. The genomic analysis showed that none of the strains possess mechanisms of virulence or resistance to transmissible antibiotics, so it is interpreted that these strains are harmless to both living beings and the environment. The type strains are SAICEU11T (=DSMZ T=CECT T) for Bacillus pretiosus and SAICEU22T (=DSMZ T=CECT 30673T) for Pseudomonas agronomica.